Magnesium sulfate treatment for acute severe asthma in adults—a systematic review and meta-analysis - Rovsing, Alma Holm; Savran, Osman; Ulrik, Charlotte Suppli (Frontiers in Allergy, 2023)
Introduction Add-on magnesium sulfate (MgSO4) for refractory asthma exacerbation has been much debated. The aim of this review and meta-analysis is, therefore, to provide an update on the current evidence for the efficacy of MgSO4 in exacerbations of asthma in adults refractory to standard of care treatment. Methods A systematic review was performed in accordance with the PRISMA guidelines. The search was performed in the PubMed database (updated April 2023). For the meta-analysis, a random-effects model was applied using the metaphor package for RStudio (RStudio, Inc.). Results A total of 17 randomized controlled trials were included. Three of the nine studies addressing treatment with intravenous (IV) MgSO4 found a significant effect on lung function compared to placebo. Of the eight studies investigating hospital admission rate, only two found a significant effect of MgSO4. Six of the nine studies investigating treatment with nebulized MgSO4 compared to placebo found a favorable effect on forced expiratory volume in 1. second (FEV1) and peak expiratory flow rate (PEF). Only two of the five studies investigating the effect on hospital admission rate found an effect of MgSO4. Comparing effect sizes in a meta-analysis revealed a greater effect on PEF in asthma patients treated with nebulized MgSO4 (MD, 23.57; 95% CI, −2.48 to 49.62, p < 0.01) compared to placebo. The analysis of patients treated with i.v. MgSO4 compared to placebo showed no statistically significant difference (MD, 5.49; 95% CI, −18.67 to 29.65, p = 0.10). Conclusion Up to two out of three studies revealed an effect of MgSO4 treatment for asthma exacerbation when assessed by FEV1/PEF, but fewer studies were positive for the outcome of hospital admissions.